Best management practices for the transition to a water-sensitive city in the South of Portugal - Rodrigues, Miguel (2021)
The uncertainty that arises from future environmental and climatic challenges requires new approaches towards urban water management in Mediterranean cities. In this work, an urban water cycle (UWC) strategy based on the best management practices (BMPs) of water-sensitive urban design (WSUD) is proposed for the transition of a coastal city in the south of Portugal into a water-sensitive city (WSC), in line with the Municipal Strategy for Climate Change Adaptation of Loulé (EMAAC of Loulé). The city’s watershed was identified using the ArcMap Hydrology toolset with geospatial data provided by Loulé’s Municipal Council Operational Unit for Adaptation to Climate Change and Circular Economy (UOACEC). A broad characterisation of the study area was conducted, identifying existing resources to further develop a SWOT (strengths, weaknesses, opportunities, threats) analysis. The Hydrology toolset outputs, precipitation events records, and survey results were used to identify flood-prone areas. The opportunities and threats identified were further used to develop the transition strategy, which is focused on critical areas identified and supported by BMPs, including source control, attenuation, treatment and infiltration measures, permeable pavements, rainwater harvesting systems, and bioretention basins. The approach is designed to increase the city’s resilience to climate extremes, as well as community engagement towards UWC management.